Growth and metabolic characterization of four lactic acid bacteria species isolated from rice beer prepared in Assam, India. Issue 4 (29th May 2019) - Das, Arup Jyoti; Das, Manas Jyoti; Miyaji, Tatsuro; Deka, Sankar Chandra
Abstract : Isolation and identification of lactic acid bacteria (LAB) from rice beer prepared in Assam, India was performed and their growth associated and functional properties were studied. LAB strains were identified as Lactobacillus casei, Pediococcus pentosaceus, Lactobacillus pentosus and Lactobacillus plantarum based on 16 s rRNA sequencing. Their growth characteristics at different pH, NaCl concentration, temperature and presence of carbohydrates were profiled. High tolerance against acid and bile salts was shown by all the strains, particularly L. pentosus TEZU174 and P. pentosaceus TEZU199 up to a pH of 1.5, and L. pentosus TEZU174 up to 14  % bile concentration. They were susceptible towards the common antibiotics, wherein erythromycin, chloramphenicol and linezolid were the most effective. The strains displayed antibiosis activity against Escherichia coli and Staphylococcus aureus and antioxidant activity in terms of resistance to H2 O2, scavenging of ·OH and DPPH free radicals was also displayed, wherein L. casei TEZU374 and P. pentosaceus TEZU482 were the most effective with above 70  % scavenging activity. The strains displayed cellular aggregation and L. casei TEZU262 and L. casei TEZU309 were highly aggregated, which attained 100  % autoaggregation within a period of 5 h. High cell surface hydrophobicity was shown by L. casei TEZU309 towards xylene and chloroform, and P. pentosaceus TEZU427 towards ethyl acetate. The strains evinced good gut tolerance capacity, antioxidant activity and adherence properties, which are characteristics of probiotic bacteria and thus are candidates for therapeutic uses and also to be used as starter cultures.